Development of Mathematical Model of Rotary Kiln which are used for Design Conventional Control Systems - Bojja, Polaiah; Merrin Prasanna, N (International Journal of Engineering and Technology, 2018)
The main aim of the work is used to develop the mathematical model which are used to design conventional control system for the real time cement plant to control several variables of a cement rotary kiln in the plant. A cement rotary kiln is a non linear distributed process which has a highly complex dynamic behavior due to chemical reaction, development of a system to understand the behavior of a kiln process as mathematical model based on control scheme for cement rotary kiln processes. However , the variables are back-end temperature,pre heater temperature, oxygen content and CO2 gas content of the kiln are used to develop the model of the processes by the most use of Automation. The proposed controller uses a PI controller and PID controller. Finally the designed of Controller scheme for cement rotary kiln process of results are car- ried out by MATLAB software for evaluation of the performance kiln process.Â